Quality indicators for the care of older adults with disabilities in long-term care facilities based on Maslow's hierarchy of needs - Taomei Zhang; Ying Liu; Yaling Wang; Chunhui Li; Xiyu Yang; Li Tian; Yin Wu; Lu Lin; Huiling Li (Elsevier, 2022)
Purpose: This study aimed to develop quality indicators for the care of older adults with disabilities in long-term care facilities (LTCFs) based on Maslow's hierarchy of needs. Methods: The draft of the quality indicators was drawn up based on a literature review and research group discussion. The quality indicators were finalized by two rounds of expert consultation (involving 15 experts) using the Delphi method. The Analytic Hierarchy Process was applied to calculate the indicators' weight. Results: The response rates of the two rounds of consultation were 100% and 93%, and the expert authority coefficients were 0.86 and 0.87. After two rounds of consultation, the expert opinion coordination coefficients of the first-, second- and third-level indicators were 0.42, 0.25, and 0.96, respectively (P < 0.05), and the variation coefficient was ≤0.25. The final quality indicators for the care of older adults with disabilities in LTCFs included 7 first-level, 19 second-level, and 107 third-level indicators. Conclusion: The quality indicators for the care of older adults with disabilities in LTCFs are reliable, scientific, comprehensive, and practical and specify the content of person-centered care needs. This can provide a reference for evaluating and improving care quality in LTCFs.